Digital Self-Regulation, Workplace Agility, and Technostress: A Sequential Pathway to Employee Productivity in Emerging Economies - Eka Suhartini; Alim Syariati (International Journal of Applied Business and International Management, 2025)
This study aims to examine how self-regulation influences employee productivity in digitally intensive work environments by incorporating workplace agility and technostress as mediating mechanisms. Extending the Job Demands–Resources framework, this study contributes by conceptualizing self-regulation as a dual-function personal resource that enhances adaptive capacity while simultaneously increasing exposure to technostress, thereby challenging linear assumptions in digital workforce research. Using a quantitative explanatory design, data were collected from 183 employees in technology-driven settings and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that self-regulation significantly increases workplace agility and technostress, while workplace agility further enhances both technostress and productivity. Technostress also exerts a positive effect on productivity, indicating the presence of functional strain. Mediation analysis confirms complementary and sequential pathways linking self-regulation to productivity. These findings imply that organizations should cultivate self-regulation and agility while managing technostress as a productive, yet controlled, pressure.